Protective prototype-Beta and Delta-Omicron chimeric RBD-dimer vaccines against SARS-CoV-2 - Xu, Kun; Gao, Ping; Liu, Sheng; Lu, Shuaiyao; Lei, Wenwen; Zheng, Tianyi; Liu, Xueyuan; Xie, Yufeng; Zhao, Zhennan; Guo, Shuxin; Tang, Cong; Yang, Yun; et al. (Cell, 2022)
Breakthrough infections by SARS-CoV-2 variants become the global challenge for pandemic control. Previously, we developed the protein subunit vaccine ZF2001 based on the dimeric receptor-binding domain (RBD) of prototype SARS-CoV-2. Here, we developed a chimeric RBD-dimer vaccine approach to adapt SARS-CoV-2 variants. A prototype-Beta chimeric RBD-dimer was first designed to adapt the resistant Beta variant. Compared with its homotypic forms, the chimeric vaccine elicited broader sera neutralization of variants and conferred better protection in mice. The protection of the chimeric vaccine was further verified in macaques. This approach was generalized to develop Delta-Omicron chimeric RBD-dimer to adapt the currently prevalent variants. Again, the chimeric vaccine elicited broader sera neutralization of SARS-CoV-2 variants and conferred better protection against challenge by either Delta or Omicron SARS-CoV-2 in mice. The chimeric approach is applicable for rapid updating of immunogens, and our data supported the use of variant-adapted multivalent vaccine against circulating and emerging variants. [Display omitted] •A chimeric RBD-dimer immunogenic approach can be used to rapidly adapt SARS-CoV-2 variants•Chimeric RBD-dimers elicit broader responses to variants compared with homodimers•Prototype-Beta chimeric vaccine is protective in both mice and macaques•Delta-Omicron chimeric vaccine protects mice from either Delta or Omicron challenge Vaccine immunogens designed as chimeras of the spike protein receptor-binding domain of two distinct SARS-CoV-2 variants elicit broad serum neutralization and protection from infection by the Beta, Delta, and Omicron variants in mice and macaques. The chimeric approach is applicable for rapid updating of immunogens against both circulating and emerging variants.